Use of videos in science dissemination activities about black holes and gravitational waves - Pereira Neto, João; Teixeira, Ricardo Roberto Plaza (Revista Hipótese, 2022)
This research analyzed the didactic use of audiovisual presentations of scientific dissemination for the teaching of astronomy themes, such as black holes and gravitational waves, in which short videos and scenes from films and documentaries were used. The investigation carried out was characterized as exploratory and qualitative, through an interrogative and reflective process, seeking to understand the facts observed to point to new possibilities for scientific education. The scientific dissemination actions carried out indicated a great interest by students in astronomy and astrophysics themes.
Keywords: Dissemination of science; Astronomy; Audiovisual resource; History of science